Let $y^2-x^3 = c$ be Bachet's equation and pretend $(x,y)$ is a solution.

The tangent at $(x,y)$ of Bachet's curve is going to intersect it in a unique new point whose coordinates are supposed to yield the so-called "duplication formula":


I have not been able to re-derive this formula no matter how hard I try. It just won't work. Attempt:

Let $f(x,y)=y^2-x^3-c$, then the curve is implicitly parametrized by $f(x,y)=0$. The gradient of $f$ at $(x,y)$, which is $(-3x^2,2y)$, is orthogonal to the curve at $(x,y)$.

Therefore, the equation of the tangent is $-3x^2(X-x)+2y(Y-y) = 0$

(I'm looking at the only line orthogonal to the gradient at $(x,y)$ going through $(x,y)$)

So, if $(X,Y)$ is the coordinates of the point of intersection I'm looking for, it should be the unique solution (different from $(x,y)$), of the following conditions:

$-3x^2(X-x)+2y(Y-y) = 0$ and $Y^2 - X^3 - c = 0$

with the assumption that, of course, by hypothesis, $y^2 - x^3 = c$

Is my reasoning sound until now?

Mathematica does not seem to agree with me, but it could be that the full-simplify function isn't sophisticated enough (it does not reduce to Bachet's formula)

FullSimplify[Solve[{2*y*(Y - y) - 3*x^2*(X - x) == 0,
    Y^2 - X^3 - c == 0}, {X, Y}], y^2 - x^3 == c]

I'm not expecting anybody to actually carry out the tedious calculations, though if somebody can manage to make Mathematica or some other software spit out the formula on its own I would be happy as I am trying to program an algorithm which automatically takes a curve in and finds the formula


Your reasoning is correct. Substitute $Y = \dfrac{3x^2}{2y} X - \dfrac{x^2 - 2c}{2y}$ into $Y^2 = X^3 + c$ to obtain a cubic for $X$. Just don't brute force it. The key point is to observe that two of its roots are known, and equal to $x$ (do you see why?). Use a sum of roots theorem to get the third one.

BTW, to use the sum of roots, yo don't need the entire cubic, but just the coefficient at $X^2$, which is $\dfrac{9x^4}{4y^2}$. Now the root you are interested in is indeed $$\dfrac{9x^4}{4y^2} - 2x = \dfrac {9x^4 - 8xy^2}{4y^2} = \dfrac{9x^4 - 8x(x^3 + c)}{4y^2} = \dfrac{x^4 - 8cx}{4y^2}$$

Proceed for $y$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.